Salovum Egg Yolk Containing Antisecretory Factor as An Adjunct Therapy in Severe Cholera in Adult Males: A Pilot Study (Journal of Health, Population and Nutrition, 2011)
Cholera involves stimulation of intestinal secretory process in response to cholera toxin leading to profuse watery diarrhoea that might cause death due to dehydration unless timely rehydration therapy is initiated. Efforts to identify and test potential antisecretory agents are ongoing. Antisecretory factor (AF) is a naturally-occurring protein produced in the human secretory organs, including the intestine, with antisectory properties demonstrated in animal and human models of secretory diarrhoea. Salovum egg yolk powder contains antisecretory proteins in a much higher (500 times) concentration than that of normal hen eggs. This is achieved by feeding hens with specially-processed cereals, capable of inducing antisecretory proteins in the yolk. The aim of the study was to examine the effect of Salovum egg yolk powder containing AF in the treatment of adult cholera patients. In an open, randomized controlled trial (pilot study), 40 adult male patients with severe cholera were studied: 20 received standard treatment (oral rehydration solution, antibiotic, and usual hospital diet) plus Salovum egg yolk powder (study group) and 20 received standard treatment alone (control group). All the patients received tablet doxycycline (300 mg) once immediately after randomization. Written informed consent was obtained from each subject before enrollment. The main outcome measures were stool weight and duration of diarrhoea. The demographic and baseline clinical characteristics of the study patients were comparable between the groups. No significant differences were found in the mean stool weight, g/kg of body-weight during the first 24 hours [study vs control group, mean±standard deviation (SD), 218±119 vs 195±136], second 24 hours (mean±SD, 23±39 vs 22±34), and cumulative up to 72 hours (mean±SD, 245±152 vs 218±169). The duration (hours) of diarrhoea after admission in the hospital was also similar in both the groups (mean±SD, 33±14 vs 32±10). No adverse effect was observed. Salovum egg powder containing AF as an adjunct therapy in the treatment of severe cholera could not demonstrate any beneficial effect. Further studies with higher doses of Salovum egg yolk powder might be considered in future to establish its antisecretory effect. Key words: Antisecretory agents; Cholera; Salovum egg yolk powder; BangladeshDOI: http://dx.doi.org/10.3329/jhpn.v29i4.8443 JHPN 2011; 29(4): 297-302